Overcoming COVID-19 in Bhutan lessons from coping with the pandemic in a tourism-dependent economy (Asian Development Bank, 2021)
Assesses the Government of Bhutan's financial relief measures for the most affected people, as well as programs and other interventions to address the impact of the coronavirus disease (COVID-19) pandemic.